STIMUL OF TRADITION - Abdul Rahim; Wimbrayardi Wimbrayardi; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2016)
Sijobang Art formerly acted as an introduction to Kaba ( news ) , stories and information presented in an art show . Media used in the performing arts is sijobang flick lighters in a manner that serves as a regulator of the rhythm . Music is not only an audio work is in production with a musical instrument that is in production . Even though a match can be a medium of entertainment for the people but as the development of the arts basijobang start using media kucapi ( lute ) . work